Service design : process and methods - Curedale, Robert, ....- (Los Angeles : Design Community College, 2016)
Service design is an emerging competence for all designers who are serious about their careers. Service design is about making services desirable, efficient and usable. We are immersed in services every day. We use the Internet, watch television, travel, bank, shop, drink coffee and eat at restaurants, use government services, and we go to movies. Over the last 50 years, the United States has evolved from an economy based on creating goods to one based on providing services. Design is no longer about only the aesthetics or surfaces of things. Today designers create diverse and complex systems of experiences of products, services, spaces and touchpoints – the people, information, products and spaces that customers encounter. In this book are the practical methods, processes, and tools that service designers use. Learn here how to understand your customers' service journey, how to develop new services and how to prototype and test your ideas for real customers in the most efficient